Hubungan Antara Koordinasi Mata-mata dan Kelentukan Togok Dengan Hasil Pukulan Clear pada Siswa Putra Ekstrakurikuler Bulutangkis di SMP Negeri 4 Muara Enim - Pahlepi, Nero; Lubis, Patricia Hotma Minar; Oktariyana, Oktariyana (ANTHOR: Education and Learning Journal, 2023)
The problem in this study is whether there is a relationship between eye-hand coordination andstriking flexibility with the results of hitting clears on male badminton extracurricular students atSMP Negeri 4 Muara Enim? The purpose of this study was to find out how much the relationshipbetween eye-hand coordination and the flexibility of the kick with the results of clear shots in malebadminton extracurricular students at SMP Negeri 4 Muara Enim. The research method used wascorrelational. The population is 12 male students who take part in badminton extracurricularactivities at SMP Negeri 4 Muara Enim. Sampling used a total sampling technique, in which thesample used was the entire population of 12 male extracurricular badminton students at SMPNegeri 4 Muara Enim. The data collection technique in this study was an eye-hand coordination test by throwing the ball against the wall, striking flexibility through the sit and reach test and clear results through the smash test. The analysis technique uses the multiple correlation formula. Based on the results of the analysis, it shows that the correlation coefficient between eye-hand coordination (X1) and flexibility of the stick (X2) with the result of a clear shot (Y) is Ryx12 = 0.66. This value indicates a strong level of relationship based on the value of the r-valueinterpretation table because it is between 0.60-0.799. This shows that there is a significantrelationship between hand-eye coordination (X1) and torso flexibility (X2) with a clear result (Y).This proves the alternative hypothesis (Ha) that the authors propose, namely that there is asignificant positive relationship between hand-eye coordination (X1) and flexibility of the toe (X2)with the result of a clear hit (Y) in badminton extracurricular students at SMP Negeri 4 MuaraEnim is proven. correct and acceptable.